2017
DOI: 10.1002/bjs.10557
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after bariatric surgery in a national cohort

Abstract: Despite clear national and international guidelines, long-term follow-up after bariatric surgery is poor, especially for young men with poor early follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 33 publications
3
53
0
Order By: Relevance
“…The 5y-Ad-DiaRem should be further evaluated in an increased number of patients lacking a full 1-year follow-up. Loss of patients to follow-up remains a major issue in the bariatric setting, which can reach 50% of patients at 5 years (46), and has been associated with poor weight loss outcomes. Despite this limitation, the 5y-Ad-DiaRem appeared robust when tested in three independent cohorts from different European countries, yet these were all Caucasian populations.…”
Section: Discussionmentioning
confidence: 99%
“…The 5y-Ad-DiaRem should be further evaluated in an increased number of patients lacking a full 1-year follow-up. Loss of patients to follow-up remains a major issue in the bariatric setting, which can reach 50% of patients at 5 years (46), and has been associated with poor weight loss outcomes. Despite this limitation, the 5y-Ad-DiaRem appeared robust when tested in three independent cohorts from different European countries, yet these were all Caucasian populations.…”
Section: Discussionmentioning
confidence: 99%
“…achieving DR) as compared to post-VSG patients 47 . Even in patients not reaching DR, a significant improvement of glycemic control is nevertheless observed, as evidenced by the reduction in HbA1c 48,49 or the number of glucose lowering agents needed to reach the HbA1c target 50 .…”
Section: Bariatric Surgery and Type 2 Diabetes Improvementmentioning
confidence: 99%
“…It is important to acknowledge the difficulty maintaining prolonged follow-up in this patient group, but routine data collection through health records would allow evaluation. In a nationwide cohort study of 16,620 patients, Thereaux and colleagues observed that follow-up rates at 1 year and 5 years decreased from 87.1 to 29.6% [33]. Factors such as male sex and younger age were predictors of poor 5-year follow-up [33].…”
Section: Discussionmentioning
confidence: 99%
“…In a nationwide cohort study of 16,620 patients, Thereaux and colleagues observed that follow-up rates at 1 year and 5 years decreased from 87.1 to 29.6% [33]. Factors such as male sex and younger age were predictors of poor 5-year follow-up [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation